Advances in Ergonomics in Design : Proceedings of the AHFE 2019 International Conference on Ergonomics in Design, July 24-28, 2019, Washington D.C., USA /: Proceedings of the AHFE 2019 International Conference on Ergonomics in Design, July 24-28, 2019, Washington D.C., USA. (2020) - Unknown
No abstract available